Advances in non-destructive evaluation proceedings of NDE 2019 - Mukhopadhyay, C. K.; Mulaveesala, Ravibabu (Singapore Springer, 2021)
This book comprises the proceedings of the Conference and Exhibition on Non Destructive Evaluation, (NDE 2019). The contents of the book encompass a vast spectrum from Conventional to Advanced NDE including novel methods, instrumentation, sensors, procedures and data analytics as applied to all industry segments for quality control, periodic maintenance, life estimation, structural integrity and related areas. This book will be a useful reference for students, researchers and practitioners.
Electronic reproduction
Keywords: Security systems; Measurement; Measuring instruments; Mathematical physics; Security Science and Technology; Measurement Science and Instrumentation; Theoretical, Mathematical and Computational Physics; Electronic books